2019
DOI: 10.3390/agronomy9090553
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Compost for Rice Cultivation Developed by Rice Industrial By-Products to Serve Circular Economy

Abstract: Rice is the major staple crop worldwide, whereas fertilization practices include mainly the application of synthetic fertilizers. A novel compost was developed using 74% of rice industrial by-products (rice bran and husks) and tested in rice cultivation in Greece’s main rice producing area. Field experimentation was conducted in two consecutive growing seasons (2017 and 2018) and comprised six fertilization treatments, including four compost rates (C1: 80, C2: 160, C3: 320 kg ha−1 of nitrogen all in split appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…By observing the net developed from the keyword co-occurrence analysis ( Figure 10 ), it can be noted that the term “bioenergy” is the most relevant. In fact, 19 percent of the articles appearing focus on the use of AWB to produce renewable energy [ 31 , 37 , 44 , 45 , 174 ] ( Figure 11 ). The terms “fertilizers” and “manures” also stand out in this net, as proven by the fact that 10 percent of the articles are about the production of fertilizers from agro-industrial by-products and their use to improve the characteristics of the cultivation soil [ 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By observing the net developed from the keyword co-occurrence analysis ( Figure 10 ), it can be noted that the term “bioenergy” is the most relevant. In fact, 19 percent of the articles appearing focus on the use of AWB to produce renewable energy [ 31 , 37 , 44 , 45 , 174 ] ( Figure 11 ). The terms “fertilizers” and “manures” also stand out in this net, as proven by the fact that 10 percent of the articles are about the production of fertilizers from agro-industrial by-products and their use to improve the characteristics of the cultivation soil [ 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten-year legacy of organic carbon in non-agricultural (brownfield) soils restored using green waste compost exceeds 4 per mille per annum: Benefits and trade-offs of a circular economy approach X [175] Bioeconomy and the production of novel food products from agro-industrial wastes and residues under the context of food neophobia 2018 X [176] The bioeconomy of microalgal heterotrophic bioreactors applied to agroindustrial wastewater treatment X [177] Camelina and crambe oil crops for bioeconomy-straw utilisation for energy 2020 X [178] The circular economy of agro and post-consumer residues as raw materials for sustainable ceramics X [50] Cellulolytic enzyme production from agricultural residues for biofuel purpose on circular economy approach 2019 X [179] The management of agricultural waste biomass in the framework of circular economy and bioeconomy: An opportunity for greenhouse agriculture in Southeast Spain X X [7] Co-digestion of by-products and agricultural residues: A bioeconomy perspective for a Mediterranean feedstock mixture 2020 X [180] The potential of plantain residues for the Ghanaian bioeconomy-assessing the current fiber value web X [181] By observing the net developed from the keyword co-occurrence analysis (Figure 10), it can be noted that the term "bioenergy" is the most relevant. In fact, 19 percent of the articles appearing focus on the use of AWB to produce renewable energy [31,37,44,45,174] (Figure 11). The terms "fertilizers" and "manures" also stand out in this net, as proven by the fact that 10 percent of the articles are about the production of fertilizers from agro-industrial by-products and their use to improve the characteristics of the cultivation soil [175,176].…”
Section: Specific Analysis Of the Research Related To Agricultural Waste Biomass (Awb)mentioning
confidence: 99%
“…Composting is one of the best and most sustainable methods of agricultural waste recycling because it allows reincorporating nutrients and organic matter into circulation while maintaining the waste-soil-plant production continuum (Jakubus 2020). The use of compost is within the scope of a sustainable agricultural system that provides an ecologically healthy and economically viable crop production, especially when the latter derives from low-value by-products of the cultivated plants (Kadoglidou et al 2019). From an economic perspective, it should be underlined that raw materials used for composting are easily available locally.…”
Section: Implications For Circular Economy and Organic Farmingmentioning
confidence: 99%
“…There are multiple current and proved experiences of successful recycling of agricultural waste through composting. For example, Kadoglidou et al (2019) reported that the application of compost from rice by-products on rice paddy fields satisfies crop nutrient requirements, without compromising yield and quality. Meanwhile, Duque-Acevedo et al (2020) reported that self-management of horticultural waste by composting is profitable at real scale.…”
Section: Implications For Circular Economy and Organic Farmingmentioning
confidence: 99%
“…Rice cultivation provides the main source of subsistence for almost half of the world population; then, several studies aim to recycle rice residues such as straw, bran, and husk. These crop residues can be used to produce for instance new biofertilizer through composting [2,3], new materials for healthy buildings and energy (e.g., biofuels). The rice, duck, fish integrated farming [4] is another well-known system for which circular principles are present.…”
Section: Introductionmentioning
confidence: 99%